ALTERNATIF SOLUSI OPTIMALISASI SUMBER DAYA MANUSIA DI PUSKESMAS WONOREJO SAMARINDA - Vandela, Zilva Kristin; Nurhasanah Nurhasanah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Wonorejo Community Health Center in Samarinda faces a specific human resource management challenge: the absence of an ambulance driver, which causes delays in emergency patient referrals. This article discusses alternative solutions to improve the efficiency and effectiveness of the workforce at the health center. The methods used include workforce needs analysis through interviews, observations, and document studies, as well as staff training and competency development. The results show improved staff performance and job satisfaction after implementing solutions such as recruiting a new driver and training internal staff. In conclusion, appropriate human resource management strategies can enhance the quality of health services, particularly in emergency referral handling.